Kemampuan Digitalisasi Bahan, Media dan Evaluasi Pembelajaran Guru SMK - Suamrdi, Kamin; Abdullah, Ade Gafar; Rohendi, Dedi (Lembaga Dongan Dosen, 2023)
Teacher competence, especially vocational schools, must continue to be updated and improved so that they can continue to keep pace with advances in knowledge and technology. The ability of teachers to make materials, media and evaluation of digital-based learning needs to be improved so that learning can run well. This ability must be mastered by teachers, especially vocational school teachers who have practical subjects. The purpose of this training is to improve the digital competence of SMK teachers in making materials, media and evaluation of learning. The training uses participatory and collaborative methods with the concept of in-house training. The results of the training obtained are that teachers have knowledge, understanding, and competence in making displays, materials, assignments, exercises, job sheets, practice guides, videos, e-modules, tests and evaluations in preparing the teaching and learning process. As many as 88.3% of Pangandaran State Vocational School teachers have basic digital competencies in preparing materials, media and learning evaluations. The information technology facilities owned by the school are very good in supporting the digital competence of teachers. Teaching materials, media and evaluation of digital learning can be used to support and strengthen students' understanding in accordance with the subject matter being taught